The perspectives of asylum seekers when accessing sexual health services in Cork and Kerry. (30th September 2020) - Jones, M M; Barry, F; Davoren, M P
Abstract: Background: The World Health Organisation (WHO) states that; "Sexual health is a state of physical, mental and social well-being in relation to sexuality. It requires a positive and respectful approach to sexuality and sexual relationships, as well as the possibility of having pleasurable and safe sexual experiences, free of coercion, discrimination and violence." Asylum seekers are among many vulnerable groups that may face inequalities in terms of sexual health and how sexual health services are accessed. The aim of the present study is to gain an understanding of the experiences of asylum seekers when accessing sexual health services in Cork and Kerry, including the perceived barriers to and factors that facilitate access. Methods: This is a qualitative study in which data was collected from 14 semi-structured interviews conducted with asylum seekers between May and June 2019. Participants were over the age of 18 and living in direct provision in Cork or Kerry. The present study uses a content analysis to explore the perspectives of asylum seekers when accessing sexual health services in Cork and Kerry. Results: Participants demonstrated varying levels of understanding around the topic of sexual health and sexual health services. Several barriers and facilitators were identified which can be grouped into socioeconomic, political/legal, systemic, and social/cultural/religious barriers and facilitators. Conclusions: The findings from this study highlighted several areas for improvement in the provision of information and services in relation to sexual health for asylum seekers living in direct provision and revealed the importance of addressing these issues in order to fulfil the purpose of public health by promoting health, preventing disease and prolonging life for all aspects of society. Key messages: This study has identified the barriers and facilitators to accessing sexual health services in the context of the direct provision system in the Republic of Ireland. The results of the study reveal the varying ideas and understanding of the topic of sexual health and how this can influence help-seeking behaviour.